CONTROVERSIAL QUESTIONS ABOUT THE IDEOLOGICAL ORIGINS OF THE PENNSYLVANIA SYSTEM OF PRISON DISCIPLINE - Олена Сокальська (Правові горизонти, 2023)
The present article delves into the origins and theoretical underpinnings of the carceral model of corrective punishment at Walnut Street Prison and the system of solitary confinement at Eastern State Penitentiary. The central research question to the extent to which the ideology advocated by the Society of Friends served as a formative influence in shaping the Pennsylvania system of prison discipline and its implementation in practice, as frequently acknowledged in historiography. To probe this inquiry, we have resorted to primary source materials and literature addressing the historical trajectory of penal institutions in Pennsylvania. It has been ascertained that the contention positing the pivotal involvement of the Society of Friends in the reformatory initiative gained traction primarily within the European penitentiary discourse on penology, through accounts of American prisons penned by La Rochefoucauld, Niemcewicz, Beaumont, and Tocqueville. The carceral model at Walnut Street Prison, characterized by distinctive attributes encompassing segregated confinement, hard labor, distinct treatment protocols grave for the most egregious of offenders, and administrative oversight by the Board of Inspectors, largely adhered to the English carceral model of corrective punishment. The conviction in the redemptive potential of seclusion was intrinsic to both religious and materialist penitentiary discourses of the era. Therefore, the ideology of the Society of Friends was not determinative here. The establishment of the system of separate and solitary confinement during the 1820s was instigated by the challenges encountered within the carceral model of Walnut Street Prison. It was a complex process and cannot be reduced to the realization of one religious group’s idea: it took into account the practical experience of prisons in Pennsylvania and other states, the theoretical research, and analyzed statistical data. The reform was predated by active public discourse and scholarly dialogues appraising the merits and limitations inherent in diverse models of prison discipline.